Pengaruh Prosedur Kredit, Kualitas Pelayanan, Dan Informasi Akuntansi Terhadap Keputusan Kredit Nasabah UMKM PT. Bank BPD Bali - I Made Adi Suhendra; Anantawikrama Tungga Atmadja; I Putu Gede Diatmika (Universitas Pendidikan Ganesha, 2023)
Abstract This study aims to examine and analyze the effect of credit procedures, service quality, and accounting information on credit decisions of MSME customers of PT. Bank BPD Bali. The data collection method in this study used a questionnaire with a Likert scale. The research population was 534 MSME credit borrowers at Bank BPD Bali Singaraja Branch from 2017 to September 2021. The MSMEs studied were MSMEs that had just borrowed credit and extended credit during the covid 19 pandemic. The number of research samples was 229 respondents. Data analysis used SEM-PLS (Structural Equation Modeling-Partial Least Square). The results show that credit procedures have a positive and significant effect on credit decision makers for MSME customers, service quality has a positive and significant effect on credit decision makers for MSME customers, accounting information has a positive and significant effect on credit decision makers for MSME customers. It can be explained that accounting information is the most important factor in addition to credit procedures and service quality in making credit decisions for MSME customers at Bank BPD Bali. Keywords : Accounting Information; Credit Decision; Service quality; Credit Procedure.